Culture-Based Justice: Legal Decisions on Forest and Land Fires by Indigenous People with Local Wisdom Approach in the Middle Sentence - Juriyah Sadjid; Kumpiady Widen; Heriamariaty Heriamariaty; Hendrik Segah (AIBPM Publisher, 2024)
The complex interaction between formal legal systems and indigenous local wisdom in managing forest and land fires in Central Kalimantan highlights the need for a nuanced regulatory approach. This study aims to explore how local wisdom is integrated into the formal legal framework governing forest and land fires by indigenous communities in the region. Conducted from September 2023 to April 2024, the research employed qualitative methods, including purposive sampling through interviews, observations, and field studies on local wisdom, focusing on community members and government agencies in Gunung Mas and Murung Raya regencies. The findings reveal that legal decisions concerning forest and land fires must incorporate the deep-rooted traditions and practices of indigenous communities, particularly those of the Dayak people. Their traditional agricultural practices and rituals, including pre-land use ceremonies, are integral to land management and fire prevention. This study concludes that aligning legal frameworks with local wisdom not only respects cultural heritage but also enhances the effectiveness of fire management policies. The implications suggest that policies should integrate traditional practices to create a more adaptive and sustainable legal system